Advanced manufacturing technology : selected, peer reviewed papers from the 3rd International Conference on Manufacturing Science and Engineering (ICMSE 2012), March 27-29, 2012, Xiamen, China - Chen, Wenzhe, (Mechanical engineer) (Advanced materials research ;, 2012)
The present volumes contain comprehensive up-to-date and cutting-edge world-wide research results on manufacturing science and engineering, focusing on Advanced Manufacturing Technology. The 672 peer-reviewed papers are grouped into 21 chapters: Surface Engineering/Coatings; Modelling, Analysis and Simulation of Manufacturing Processes; Materials Forming; Materials Machining; Welding & Joining; Material Design of Computer Aided Manufacture; Microwave Processing of Materials; Thermal Engineering Theory and Applications; CAM/CAE; High-Speed/Precision Machining and Inspection Technology; Micro-Ma.